Examining etiological pathways to necrotizing enterocolitis in very preterm infants. Issue 2 (April 2021) - Everhart, Kayla C.; Donevant, Sara B.; Wirth, Michael D.; Dail, Robin B.
Abstract: Preterms have increased morbidity and mortality due to immature physiology; necrotizing enterocolitis (NEC) is a devastating gastrointestinal morbidity. Researchers have found an association between the incidence of NEC and infusing packed red blood cell (PRBC) transfusions. Others postulate NEC results from feeding infants during PRBC transfusion. Our team speculates the temperature of the PRBCs may result in central hypothermia, which contribute to the incidence of NEC. This scoping literature review examined studies including PRBC transfusions, enteral feedings, anemia and/or hypothermia in relationship to NEC. From 846 publications found, 749 were removed from title screening and duplication, 42 full reports were read and assessed. Ten final studies were synthesized. Studies revealed mixed conclusions as to the relationship of PRBC transfusions and NEC in preterms. No published studies evaluated body temperature or PRBC temperature in relationship to NEC. The etiology of NEC related to PRBC transfusions remains elusive and prompts further research.